MENINGKATKAN PENGETAHUAN PROFESIONAL GURU PADA ABAD KE 21 MELALUI PELATIHAN GURU BAHASA INGGRIS (Jurnal Pengabdian Kepada Masyarakat (ABDIMAS) Universitas Baturaja, 2023)
To improve teacher competence in learning English, it can be improved through training. Thisactivity was carried out at the Muhammadiyah University of Palangkaraya and IAIN Palangka Raya byface-to-face eight times (8x) meetings in August 2022 - January 2023 attended by 26 teachers fromvarious madrasah and Islamic boarding schools at MTs and MA levels under the auspices of the Ministryof Religion of Kalimantan Tengah Province. They accompanied by 5 trainers and a Master Trainer. At theend of the ELTT Batch I activities in 2022, 26 teachers had successfully completed this program andreceived competency certificates equivalent to 100 JP. Through this activity, it was hoped that Englishteachers throughout Indonesia will gain valuable experience in interactive methods of teaching, be moreconfident, and have a strong professional network. It is hoped that in the next batch, the quota for Englishteachers will be opened to the public. So that teachers who live outside the city of Palangka Raya (in theProvince of Central Kalimantan) can join this program.